Applying mass spectrometric methods to study androgen biosynthesis and metabolism in prostate cancer - Knuuttila M; Hamalainen E; Poutanen M (BIOSCIENTIFICA LTD, 2022)
Recent development of gas chromatography and liquid chromatography-tandem mass spectrometry (GC-MS/MS, LC-MS/MS) has provided novel tools to define sex steroid concentrations. These new methods overcome several of the problems associated with immunoassays for sex steroids. With the novel MS-based applications we are now able to measure small concentrations of the steroid hormones reliably and with high accuracy in both body fluids and tissue homogenates. The sensitivity of the tandem mass spectrometry assays allows us also for the first time to reliably measure picomolar or even femtomolar concentrations of estrogens and androgens. Furthermore, due to a high sensitivity and specificity of MS technology, we are also able to measure low concentrations of steroid hormones of interest in the presence of pharmacological concentration of other steroids and structurally closely related compounds. Both of these features are essential for multiple preclinical models for prostate cancer. The MS assays are also valuable for the simultaneous measurement of multiple steroids and their metabolites in small sample volumes in serum and tissue biopsies of prostate cancer patients before and after drug interventions. As a result, novel information about steroid hormone synthesis and metabolic pathways in prostate cancer has been obtained. In our recent studies, we have extensively applied a GC-MS/MS method to study androgen biosynthesis and metabolism in VCaP prostate cancer xenografts in mice. In the present review, we shortly summarize some of the benefits of the GC-MS/MS and novel LC-MS/MS assays, and provide examples of their use in defining novel mechanisms of androgen action in prostate cancer.